Using the Robson Classification to Explain the Fluctuations in Cesarean Section - Cammu, H. (J Pregnancy, 2020)
PURPOSE: As the rate of cesarean sections (CS) continues to rise in Flanders (northern part of Belgium), it is important to understand the reasons behind this evolution and to find ways to achieve appropriate CS rates. For this analysis, we categorized CS changes between 1992 and 2016, applying the Robson 10-Group Classification System (TGCS). We also applied the TGCS to analyze the information of the only clinics where between 2008 and 2016, the absolute CS rate had fallen by more than two percent. METHODS: This paper is based on a population-based cross-sectional study. Robson's TGCS was used to analyze CS rates for the years 1992, 2000, 2008, and 2016, using the Flemish population-based birth register. RESULTS: Between 1992 and 2016, the overall CS rate increased from 11.8% in 1992 to 20.9% in 2016. The major contributors to that increase were (a) single, cephalic nulliparous women, at term in spontaneous labor (Robson group 1); (b) single, cephalic nulliparous women, at term in induced labor or CS before labor (group 2); and (c) multiparous women with single cephalic at term pregnancy with history of CS (group 5). In the subgroup of the seven clinics where the collective CS rate had decreased from 23.2% in 2008 to 19.3% in 2016, the main contributors to this decrease were Robson groups 1 and 2. CONCLUSIONS: The CS increase in Flanders between 1992 and 2016 is mainly the result of the absolute CS increase in the childbirth of nulliparous women with a single cephalic baby at term in spontaneous or induced labor and in women with a single cephalic presentation at term and a previous CS. Further research in these aforementioned groups is needed to identify the real reasons for the CS increase.